Determinants of 1-year mortality after acute myocardial infarction in patients with and without diabetes - Annalisa Montebello, MD, MRCP(UK), MSc; Martina Agius, MD; Martina Grech, MD; Nicoletta Maniscalco, MD; Ivana Kenkovski, MD; Stephen Fava, MD, MRCP(UK), FACP, FEFIM, FRCP(Lond), MPhil(Melit), PhD(Exeter) (Clinical Medicine, 2024)
The gap in excess mortality between patients with and without diabetes has not decreased over time. The aim of this study was to investigate the determinants of mortality after acute myocardial infarction (AMI) in patients with diabetes and without diabetes in a contemporary population. A retrospective analysis of a cohort of 266 patients with a diagnosis of AMI during 2022 was carried out. Patients living with diabetes had higher 1-year mortality, even after adjustment for covariates. Estimated glomerular filtration (eGFR) rate was independently associated with increased mortality in patients with diabetes. Plasma glucose was independently associated with peak troponin in patients both with and without diabetes. These data suggest that patients living with diabetes and with a low eGFR warrant more aggressive risk reduction and use of nephroprotective medications. Further studies are needed to assess whether early blood glucose control improves cardiovascular outcomes in all patients with AMI.